State and civil society in the xxi century: A look from the critical theories (2020)
This article is based on a double objective. On the one hand, to question the theoretical foundations on which the idea of the State was constructed as a presupposition of Western modernity and the implications that this has had on the current state of affairs. On the other hand, prescribe action plans from critical social theories that induce not only to redefine power relations between civil society and institutions, but also to rethink socially reproduced ideas. To accomplish this objectives, a documentary analysis is made to make a genealogy of the concept of State from the dominant social theories. © 2020, Universidad del Zulia. All rights reserved.